SISTEM PENERIMAAN KAS PADA RS PGI CIKINI - Venyka Sari Silalahi; Josephine Tobing (Buletin Ekonomi, 2018)
Cash accounting is a tool in the sense of an acceptable exchange for debt repayment and can be accepted as a deposit to the bank in the amount of nominal, as well as deposits in banks or other places that can be taken at any time. Another sense in terms of accounting, which is defined as cash is something (either in the form of money or not) that can be available immediately and is accepted as a means of settlement of liabilities at face value. Cash Receipts Accounting System is a record made for carry out activities of receiving money from cash sales or from credit are ready and free to use for general corporate activities. Accounting System Cash Receipts are cash flow process that occurs in the company is continuously throughout the life of the company concerned is still operating. Cash flow consists of cash inflows and cash flow out. Cash sales are carried out by the company by requiring the buyer to make a payment over the prices of goods before the goods are delivered by the company to the buyer. The goal of establishing the company is to make a profit, because profit is expected for an all company. For get optimal profit corporation guided in its operation to work effectively and efficiently in the use of economic resources. To maintain the smooth operation of the company, the company should be able to apply a good accounting system acceptance, and reduce irregularities that may occur in the operational activities of the company. To reduce the deviation, it is necessary supervision and inspection of suppliers regularly about "whether the cash receipt system analysis has been run in accordance with the applicable.â€ Once the money is received by the company, and then handed over to the buyer of goods and cash sales transactions recorded by the company later. RS PGI Cikini have a policy and objectives which are used as a guide at the time of receipt of goods to ensure that goods ordered received in outlet properly by ensuring data entry and reception of goods has been done correctly and accurately so as not occurrence abuse of authority and easy setup goods in the warehouse to the outlet / stockist..Keywords : Cash, Receipts, Receivable